Exploring the acceptability, and feasibility of a modified virtual reality-based AVATAR therapy in schizophrenia spectrum disorders: A case series report - Edit Vass; Lilla Gerlinger; Luca Egervári; Tünde Kilencz; Gábor Csukly; Levente Hermán; János Réthelyi; Kinga Farkas; Lise Mariegaard; Louise Birkedal Glenthøj; Lajos Simon (Acta Psychologica)
Schizophrenia spectrum disorder poses a complex challenge in psychiatric treatment due to its multifaceted symptomatology. Modified AVATAR therapy, an innovative virtual reality-based intervention integrating Cognitive Behavioral Therapy (CBT) techniques such as systematic desensitization, and Acceptance and Commitment Therapy (ACT) approach offers a promising avenue for addressing auditory verbal hallucinations (AVH). This case series report investigates the acceptability and feasibility of a modified AVATAR therapy in three patients diagnosed with schizophrenia spectrum disorder who experience distressing AVH. The study provides detailed demographic and clinical information, outlines the modified AVATAR therapy protocol, and presents outcomes measured through standardized assessments.The findings indicate a decrease in the severity of AVHs, along with enhancements in overall symptomatology after modified AVATAR therapy sessions. Moreover, qualitative perspectives from patients shed light on their favorable experiences and perceptions of this adapted intervention. Nonetheless, the results exhibited inconsistency across individual cases, underscoring challenges for future research and clinical applications in this domain. Nevertheless, in light of the hurdles accompanying the rehabilitation of schizophrenia patients, along with the evaluation and subsequent measurement of parameters affecting efficacy, modified AVATAR therapy could present a valuable addition to schizophrenia patient care.